1994
DOI: 10.1088/0960-1317/4/3/001
|View full text |Cite
|
Sign up to set email alerts
|

A study of wear on MEMS contact morphologies

Abstract: The fabrication of many micro electro mechanical systems (MEMS) is mainly based on silicon and its compounds and, for moving structures such as micromotors, tribological behaviour plays a key role in the performance. In this paper the wear of MEMS-compatible materials has been investigated for a range of contact areas and contact forces typical of MEMS. Special test specimens incorporating a range of micromachined micro structures on their top surfaces have been fabricated in order to simulate those conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Microactuators (microturbines, micromotors, microvalves, microtools, etc.) produced by microstructure technology include solid surfaces that interact and move relative to one another, with the dimensions of such components being in the range of a few 100/zm only and those of individual structures much less than that [4][5][6]. Many micromechanical components are based on monocrystalline, or less frequently on polycrystalline, silicon and often combined monolithically with microelectronic devices to produce sophisticated microsystems.…”
Section: Introductionmentioning
confidence: 99%
“…Microactuators (microturbines, micromotors, microvalves, microtools, etc.) produced by microstructure technology include solid surfaces that interact and move relative to one another, with the dimensions of such components being in the range of a few 100/zm only and those of individual structures much less than that [4][5][6]. Many micromechanical components are based on monocrystalline, or less frequently on polycrystalline, silicon and often combined monolithically with microelectronic devices to produce sophisticated microsystems.…”
Section: Introductionmentioning
confidence: 99%
“…Polysilicon, a very commonly used structural material in MEMS, exhibits high friction and poor wear properties at polysilicon-polysilicon interfaces [51]- [55]. It has been demonstrated that humidity is a strong factor in the wear of rubbing surfaces in polysilicon microfabrication.…”
Section: Wearmentioning
confidence: 99%
“…Due to very low coefficient of friction and surface roughness of DLC and DLN films, the films can be act as a excellent solid lubricants of microgears or microengine based MEMS devices. Very small surface roughness can reduce the friction and wear rate in microstructure component during operations [54][55][56]. DLC coating which can improve the lifetime of linear motor actuated by electrostatic force which drive by sliding component laterally [55].…”
Section: Diamond Dlc Dln Films As Coating Materials For Memsmentioning
confidence: 99%